Analysis of clinical characteristics of mesalazine-induced cardiotoxicity - Chen, Junyu; Duan, Tengfei; Fang, Weijin; Liu, Shikun; Wang, Chunjiang (Frontiers in Pharmacology, 2022)
Background: Mesalazine is the first-line treatment for inflammatory bowel disease (IBD), but it can cause a fatal cardiotoxicity. We aimed to analyze the clinical features of mesalazine-induced cardiotoxicity and provide evidence for clinical diagnosis, treatment and prevention. Methods: We collected Chinese and English literature on mesalazine-induced cardiotoxicity from 1970 to 2021 for retrospective analysis. Results: A total of 52 patients (40 males and 12 females) were included, with a median age of 24.5 years (range 9-62) and a median onset time of 14 days (range 2-2880). Cardiotoxicity was manifested as myocarditis, pericarditis and cardiac pericarditis. The main clinical manifestations are chest pain (82.7%), fever (46.2%), respiratory symptoms such as dyspnea and cough (40.4%). The levels of troponin T, creatine kinase, C-reactive protein and other biochemical markers were significantly increased, as well as leukocyte count and erythrocyte sedimentation rate. Myocardial infarction, pericardial effusion, myocardial necrosis and other symptoms of cardiac injury are often suggested by cardiac imaging. It is important to discontinue mesalamine immediately in patients with cardiotoxicity. The use of corticosteroids in combination is a common treatment option, but the benefits remain to be determined. Re-use of mesalamine should be carefully considered as it may cause the recurrence of cardiotoxic symptoms. Conclusion: Mesalazine may cause cardiotoxicity in patients with inflammatory bowel disease, which should be comprehensively diagnosed based on clinical manifestations, biochemical indicators and cardiac function imaging examinations. For clinicians, immediate discontinuation of mesalazine and combined use of corticosteroids may an effective treatment for cardiotoxicity.